Price Expectations and Reference-Dependent Preferences - Robert Rutledge; Vinayak Alladi; Stephen L. Cheung (Institute of Labor Economics (IZA), 2022)
We experimentally test Kőszegi and Rabin's (2006, 2007) theory of reference-dependent preferences in the context of price expectations. In an incentivised valuation task, participants are endowed with a mug and provide their willingness to accept (WTA) to sell it. We manipulate the sale price in a separate, exogenous forced sale scenario, which is predicted to produce a 'comparison effect', moving WTA in the opposite direction to the forced sale price. Consistent with the theory, we observe a treatment effect of between AUD 0.79 and 2.06 in the hypothesised direction; however, it is statistically insignificant. We also elicit participants' loss aversion to account for heterogeneity in the theorised effect; however, controlling for the interaction between our treatment and loss aversion does not consistently strengthen our result.
Keywords: C91; D90; 330; reference dependence; price expectations; comparison effect; loss aversion